Open Space: The Global Effort for Open Access to Environmental Satellite Data - Borowitz (MIT Press, 2017)
Monograph
fulltext
Keywords: Aerospace; Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing; Signal Processing and Analysis; Transportation